Comparison of efficacy and safety between gonioscopy-assisted transluminal trabeculotomy and trabeculectomy for primary open-angle glaucoma treatment: a retrospective cohort study - Leyi Wang; Chen Wang; Pengyun Wang; Chenyang Dai; Rachita Kurmi; Wenzhe Zhang; Jiayin Wu; Hui Guo (BMC Ophthalmology)
Abstract Background Trabeculectomy (TRAB) traditionally has been the gold-standard surgical treatment for primary open-angle glaucoma (POAG), while gonioscopy-assisted transluminal trabeculotomy (GATT) is an emerging minimally invasive surgery used for the treatment of various open-angle glaucoma (OAG) types. In this study, we aimed to compare the efficacy and safety between GATT and TRAB for the treatment of POAG. Methods This cohort study included eyes with POAG that underwent a single GATT (30 eyes) or TRAB (34 eyes). Follow-up was conducted at 1 day, 1 week, and 1, 3, 6, and 12 months postoperatively. Intraocular pressure (IOP), the numbers of glaucoma medication, visual field mean deviation, peripapillary retinal nerve fiber layer thickness, surgical time, and complications were analyzed. Success criteria were defined as IOP ≤ 21 mmHg and ≥ 20% IOP reduction from baseline. Qualified and complete surgical success rates were also compared. Results IOP and antiglaucoma drug use decreased significantly at 12 months postoperatively in the both groups (P < 0.001), with no significant differences between the two groups pre- and postoperatively (P > 0.05). The success rates at 12 months were 70% (95% confidence interval [CI] = 52.6–87.4%) in the GATT group and 76.5% (95% CI = 61.4–91.5%) in the TRAB group (P = 0.559).Visual field loss remained unchanged at 12 months postoperatively compared with preoperative levels in both groups (P > 0.05); however, peripapillary retinal nerve fiber layer thickness decreased significantly at 12 months postoperatively compared with preoperative levels in the GATT group (P < 0.001). The most frequent complications after TRAB and GATT were bleb-related complications and hyphema, respectively. Conclusions GATT demonstrated an efficacy comparable to that of TRAB for the treatment of POAG with regards to lowering IOP, reducing medication use, and preserving visual fields. Thus, GATT is a minimally invasive technique that enables an effective and safe decrease in IOP.